Assessing the connection between organophosphate pesticide poisoning and mental health: A comparison of neuropsychological symptoms from clinical observations, animal models and epidemiological studies. (January 2016) - Stallones, Lorann; Beseler, Cheryl L.
Abstract: Psychiatry and psychology are beginning to recognize the importance of lead, mercury and heavy metals as causal partners in the development of mental disorders. Further, mental health researchers and clinicians are embracing the idea that the combined effects of genetics and environmental exposures can result in perturbations in brain neurochemistry leading to psychiatric disorders. The purpose of this review is to examine the biological foundations for the epidemiological observations previously identified by reviewing the toxicology literature and relating it to epidemiological studies addressing the role of poisoning with organophosphate pesticides (OPs) in neurobehavioral and neuropsychological disorders. The goal of this review is to raise awareness in the mental health community about the possibility that affective disorders might be the result of contributions from environmental and occupational pesticide poisoning.